Employing small games within a training program to develop some basic skills among football players in the under-17 age group - nouiri boubekaer, (sports creativity, 2025)
The objective of this study is to find out the effect of employing mini games in a training program for the development of some basic skills in football players cubs cqtegory under 17 yeqrs old.to achieve the goals of this study,we use the experimental method. The sample of the study was chosen in a deliberate manner represented by football players under 17 years old ( cubs of the sports federation of Barhoum Almmsila, the sample included 18 players were divided into two groups, the experimental one that includes (09) players and the controlling one that includes (09) players. The tests were used as a tool for field study and for statistical processing using spss program ,the results were obtained as followed: small exercises of suggested mini games have an effect on the development of some basic skills of football players under 17 years old, the recruitment of mini games in the training programs positively affect the development of some basic skills of football players Under the age of 17 years old ,the training program according to the principles and scientific basics in terms of the diversification of exercises and methods and principles of modern training reached the athlete to the highest levels and the most important suggestions are the need to pay attention to the development of basic skills in football, especially cubs under 17 years old. There must be a hard work of researchers and Algerian students in this field .in order to develop Algerian football and raise the level of sport practice